Evaluasi Penerapan Akuntansi Kontraksi Asuransi Jiwa Dalam Kaitannya Dengan PSAK No. 36 Pada PT Taspen (Persero) Cab. Bogor - Nurwita, Dwi Ria; Pamungkas, Bambang (Institut Bisnis dan Informatika Kesatuan, 2014)
Life insurance is an agreement between two (2) or more parties with the insurerand theinsured to receive payment of a premium to base a claim for death or life of someone who is insured to the insurance contract is completed. IAI (Indonesian Institute of Accountants) has published latter PSAK No. 36 was revised in 2011 on Accounting for Insurance Contracts. The purpose of this study was to determine the application of the life insurance contract accounting under PSAK No. 36 in general, both in the establishment of policies on premium income and expenses for setting policy life insurance claims on TASPEN PT (Persero) Cab. Bogor. The method used in this research is descriptive qualitative method. This research method is done by describing the rank of overall life insurance accounting and PSAK No.36. The results showed that the preparation of life insurance accounting TASPEN PT (Persero) Cab. Bogor has been prepared based on generally accepted accounting policies, and some of the related GAAP, including PSAK No.36 Accounting for Life Insurance which serve as guide lines for the recording and programming of one insurance program ENT (Annuities). Premium income TASPEN PT (Persero) derived from participant and employer contributions for ENT program. While the claims of the existing burden on TASPEN PT (Persero) is Liability for Future Policy Benefits (KMPMD), debt claims and estimated claims liability. In general TASPEN PT (Persero) Cab.Bogor have adopted regulations that refers to IFRS, especially PSAK No.36 in life insurance accounting, include the recognition, recording, and reporting of all transaction.